Thymic stromal lymphopoietin contributes to ozone-induced exacerbations of eosinophilic airway inflammation via granulocyte colony-stimulating factor in mice - Yuki Kurihara; Hiroki Tashiro; Yoshie Konomi; Hironori Sadamatsu; Satoshi Ihara; Ayako Takamori; Shinya Kimura; Naoko Sueoka-Aragane; Koichiro Takahashi (Allergology International, 2024)
Background: Ozone is one of the triggers of asthma, but its impact on the pathophysiology of asthma, such as via airway inflammation and airway hyperresponsiveness (AHR), is not fully understood. Thymic stromal lymphopoietin (TSLP) is increasingly seen as a crucial molecule associated with asthma severity, such as corticosteroid resistance. Methods: Female BALB/c mice sensitized and challenged with house dust mite (HDM) were exposed to ozone at 2 ppm for 3 h. Airway inflammation was assessed by the presence of inflammatory cells in bronchoalveolar lavage fluid and concentrations of cytokines including TSLP in lung. Anti-TSLP antibody was administered to mice to block the signal. Survival and adhesion of bone marrow-derived eosinophils in response to granulocyte colony-stimulating factor (G-CSF) were evaluated. Results: Ozone exposure increased eosinophilic airway inflammation and AHR in mice sensitized and challenged with HDM. In addition, TSLP, but not IL-33 and IL-25, was increased in lung by ozone exposure. To confirm whether TSLP signaling is associated with airway responses to ozone, an anti-TSLP antibody was administered, and it significantly attenuated eosinophilic airway inflammation, but not AHR. Interestingly, G-CSF, but not type 2 cytokines such as IL-4, IL-5, and IL-13, was regulated by TSLP signaling associated with eosinophilic airway inflammation, and G-CSF prolonged survival and activated eosinophil adhesion. Conclusions: The present data show that TSLP contributes to ozone-induced exacerbations of eosinophilic airway inflammation and provide greater understanding of ozone-induced severity mechanisms in the pathophysiology of asthma related to TSLP and G-CSF.